Tratamento hepatoprotetor favorece a resposta leucocitária de ratos wistar intoxicados por CCL4 - Belo, M. A A [UNESP]; Souza, L. M. [UNESP]; Soares, V. E. [UNESP]; Sobreira, M. F R; Casol, D. M S; Toma, S. B. (My University, 2009)
The aims of this investigation was to evaluate the effect of hepatoprotective treatments with a compound prepared by the association of N-Acetyl DL-Methionine (5%) + Choline chloride (2%) + Caffeine (1%) + Thiamine hydrochloride (1%) + Nicotinamida (0,5%)+ Pyridoxine hydrochloride (0.04%), administered through intramuscular (IM) route, at doses of 0.2, 0.6 and 1.0 mL/kg of BW, through the study of leukocytes responses in rats submitted to acute intoxication with CCl4. 147 females were randomized into 21 groups, performing five different treatments, which were evaluated seven animals in four periods: two, four, six and eight days after CCl4-induced intoxication. In this study, it was observed absolute eosinophilia and monocytosis in animals untreated and treated with the lowest dose of 0.2 mL. These responses were significantly better in animals treated with 0.6 and 1.0 mL/ kg BW. The untreated animals showed thrombocytopenia, when compared to treated animals. Absolute neutropenia and lymphocytosis was observed in all rats intoxicated with CCl4, there is no difference among treatments. The analysis of white blood cells demonstrated that the hepatoprotective treatments favored the leukocyte response, by act beneficially on the population of these cells, supporting the hypothesis that these events may reduce the deleterious effects in liver tissue after intoxication by CCl4.
Hepatoprotective treatment improves leukocyte responses of Wistar rats intoxicated by CCl4
Keywords: Carbon tetrachloride; Hepatoprotective; Leukocytes; Rats; Animalia; Rattus; Rattus norvegicus